Elementary Mandarin - Polley, Carl (Open textbook library., 2019)
This course is designed for learners with no background in Chinese. It introduces basic structures of the Mandarin Chinese language with emphasis on listening, speaking, reading and writing skills. Students will gain these four skills in standard Mandarin Chinese, attaining approximately the Novice-High level on the ACTFL-ETS (American Council on the Teaching of Foreign Languages) proficiency scale. Topics of conversation include basic greetings, names, family, work, study, and hobbies. Upon successful completion of this course, the student should be able to: Exchange information about familiar topics using phrases and simple sentences, sometimes supported by memorized language, and ask and answer simple questions about everyday situations in short social interactions. (Interpersonal Communication) Verbally convey basic information on familiar topics using phrases and simple sentences. (Presentational Speaking) Write short messages and notes on familiar topics related to everyday life. (Presentational Writing) Interpret spoken words, phrases, and simple sentences related to everyday life by recognizing pieces of information and by identifying the main topic. (Interpretive Listening) Interpret familiar words, phrases, and sentences within short and simple texts related to everyday life and identify the main idea of written materials. (Interpretive Reading)